Improving the Competence of State Civil Apparatus in the Vuca Era - Andi Ismawaty (Jurnal Hukum Volkgeist, 2022)
Indonesia is facing the Industrial Revolution 4.0 which affects aspects of human life. This era is often characterized by the condition of VUCA, which stands for Volatility (turbulence), Uncertainty (uncertainty), Complexity (complex), and Ambiguity (unclear). The importance of increasing competence in the State Civil Apparatus (ASN) and the impact of the VUCA era will also be increasingly felt. with the aim that ASN with qualified leadership qualities. This research is intended to provide management recommendations to improve the professionalism of ASN. This type of research is qualitative (doctrinal). Qualitative normative research is intended to formulate the basic problems being faced by using a measurable analytical knife. The results of this paper are recommendations for succession management which are suggested to be implemented in government agencies as well as the work culture of ASN in the future by obtaining appropriate cadres of leaders in facing the challenges of changing eras.